Skins : A Novel - Louis, Adrian C. (Book collections on Project MUSE., 2022)
"Skins is Adrian C. Louis's realistic novel of life on Pine Ridge Reservation, the story of two brothers--one a rez cop, the other an alcoholic--and their relationship with each other, with their people, with their environment"--